Implementation of the Problem-Based Learning Model to Enhance Critical Thinking Skills in Elementary Science Education - Intan Juniarmi (PT. Anagata Sembagi Education, 2025)
The development of critical thinking skills in elementary science education is essential to prepare students for twenty-first century challenges. However, conventional teacher-centered instruction often limits opportunities for students to engage in inquiry and problem-solving activities. This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model in enhancing critical thinking skills in elementary science classrooms. A quasi-experimental design with a non-equivalent control group pretest–posttest approach was employed involving two Grade 5 classes. The experimental group received PBL instruction, while the control group was taught using conventional methods. Data were collected through a validated critical thinking test and analyzed using descriptive statistics, N-Gain, paired t-tests, independent t-tests, and effect size calculations. The results indicate that the experimental group demonstrated significantly higher improvement compared to the control group, with a moderate-to-high N-Gain and a large effect size. Students engaged in structured problem-solving stages showed enhanced abilities in problem identification, analysis, evaluation, inference, and conclusion drawing. The study concludes that the PBL model is an effective instructional approach for improving critical thinking skills in elementary science education and offers a practical alternative to conventional teaching methods.